Comprehensive analysis of N6-methylandenosine regulators and m6A-related RNAs as prognosis factors in colorectal cancer - Wei Li; Yingchao Gao; Xiaojing Jin; Haobo Wang; Tianhao Lan; Ming Wei; Weitao Yan; Guiqi Wang; Zhongxin Li; Zengren Zhao; Xia Jiang (Elsevier, 2022)
Colorectal cancer (CRC) is one of the most common malignancies and has been a leading cause of cancer-related death worldwide in recent years. N6-methyladenosine (m6A) methylation is the most abundant epigenetic modification of various types of RNAs, and it plays a vital role in promoting cancer development. Here, we obtained SNV and transcriptome data of CRC from The Cancer Genome Atlas (TCGA). We demonstrated that most m6A methylation regulators were aberrantly expressed in individuals with CRC. The abnormal expression of m6A regulators was caused by their different copy number variation (CNV) patterns, and alteration of m6A regulators was significantly correlated with prognosis and tumor stage. By using weighted coexpression network analysis (WGCNA), we identified m6A-related long noncoding RNAs (lncRNAs) and mRNAs; then we used least absolute shrinkage and selection operator (LASSO) Cox regression analysis to construct m6A-related lncRNA and mRNA prognostic signatures in the TCGA dataset. Furthermore, a nomogram with clinicopathological features, lncRNA risk scores, and mRNA risk scores was established, which showed a strong ability to forecast the overall survival of the individuals with CRC in training and testing sets. In conclusion, m6A methylation regulators played a vital role in affecting the prognosis of subjects with CRC, and m6A-related lncRNAs and mRNAs revealed underlying mechanisms in CRC tumorigenesis and progression.